Evidence for functional pre-coupled complexes of receptor heteromers and adenylyl cyclase - Gemma Navarro (Nature Portfolio, 2018)
It is unclear whether GPCRs, G proteins and adenylyl cyclase (AC) associate through random collisions or defined pre-coupling mechanisms. Using a peptide-based approach, the authors show that heteromers of adenosine A2A and dopamine D2 receptors form pre-coupled complexes with their cognate G proteins and AC5.